2015
DOI: 10.1016/j.seares.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Multi-decadal variation in size of juvenile Summer Flounder (Paralichthys dentatus) in Chesapeake Bay

Abstract: During the last quarter-century, management of Summer Flounder Paralichthys dentatus along the Atlantic coast resulted in significant increases in abundance such that rebuilding targets were recently achieved. Although spawning stock biomass is high, recruitment of young-of-theyear (YOY) Summer Flounder remains variable. Chesapeake Bay is one of the principal nursery areas for this species, but processes such as growth and survival that affect production of YOY Summer Flounder in this estuary have not been exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…As noted previously, the density-dependent processes in early life history stages during years of high freshwater inflow coupled with the mismatch in the timing of the spring phytoplankton bloom and the residence period of adult alewife in the bay may yield the observed negative effect of chl a on alewife mean condition. Similarly, reductions in juvenile summer flounder growth have been observed in environments characterized by lower salinities (Nys et al 2015). The same study also found impaired growth of small summer flounder at elevated temperatures, which is consistent with the negative effect of temperature on condition given by the DFA model.…”
Section: Broad-scale Patterns In Conditionsupporting
confidence: 77%
“…As noted previously, the density-dependent processes in early life history stages during years of high freshwater inflow coupled with the mismatch in the timing of the spring phytoplankton bloom and the residence period of adult alewife in the bay may yield the observed negative effect of chl a on alewife mean condition. Similarly, reductions in juvenile summer flounder growth have been observed in environments characterized by lower salinities (Nys et al 2015). The same study also found impaired growth of small summer flounder at elevated temperatures, which is consistent with the negative effect of temperature on condition given by the DFA model.…”
Section: Broad-scale Patterns In Conditionsupporting
confidence: 77%
“…However, due to suboptimal higher water temperatures, some fish species can reduce their appetite and negatively affect growth (Benetti, Acosta, & Ayala, 1995). As in other species (e.g., P. dentatus; Nys, Fabrizio, & Tuckey, 2015) large variations in growth were observed in our study. Our growth data appear to be lower when compared to the growth of wild-caught juvenile (1 kg; Benetti et al, 1995) and slightly higher to cultured juvenile (250 g; Guartatanga, 1997) in the same period (about 365 days).…”
Section: Discussionmentioning
confidence: 97%